ANALISIS PENGARUH KOMPENSASI, KEPUASAN KERJA, KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION (STUDI PADA KONSULTAN DESIGN PT. GRAHACIPTA). - Bunga Astra Gracia (Universitas Pamulang, 2016)
ANALYSIS OF EFFECT OF COMPENSATION, JOB SATISFACTION, ORGANIZATIONAL COMMIT-MENT TO TURNOVER INTENTION (STUDY IN DESIGN CONSULTANTS PT. Grahacipta). A high turn-over rate would cause a negative impact for the Organization, it is like creating instability and uncertainty (uncertainty) against labor conditions and increase the cost of the human resources in the form of training costs which have already invested in employee recruitment and training costs to return. High Turnover also resulted in ineffective organizations because the company lost experienced employees and retraining new employees. The purpose of this research is to analyze the effect of variable compensation, job satisfaction, and organizational commitment of turnover intention and to analyze the variable that has the biggest influence of turnover intention. The sample is around 117 respondents. As for the methods used in sampling is by using census sampling method, and the analyze data use the multiple linear regression analyze, with the SPSS program assistance. The results of the testing of the hypothesis, indicating that : 1) the variable compensation have negative effect on turnover intention, 2) job satisfaction have negative effect on turnover intention, 3) organizational commitment have negative effect on turnover intention, 4) compensation, job satisfaction, organizational commitment have negative effect on turnover intention. Keywords: Compensation, Job Satisfaction, Organizational Commitment, Turnover Intention